Peer Medicine Application Supervisor: A Breakthrough for the Elimination of Scabies in Islamic Boarding School - Respati, Titik; ., Noormartany; Ahmed, Rafdi; Fauzi, Pahmi Firman; Deriansyah, Mochammad Rachmat; Nabalah, Revan Muhammad; Wijaya, Fathya Puspita; Fadia, Zulfi Noor (KnE Social Sciences, 2023)
The incidence of scabies, especially in Islamic boarding schools (Pesantren), remains a persistent problem in Bandung city. Previous studies have identified multiple contributing factors to scabies, making it difficult to eradicate. Despite efforts to introduce healthy and clean-living behaviors (PHBS) to treat and eliminate the disease, scabies continues to persist. This study aims to pilot an innovative approach called the Assigned Peer Medicine Application Supervisor (PMAS) to combat scabies in an Islamic Boarding School in Bandung city. The research involved all students, totaling 193 aged between 5 and 18 years old, consisting of 82 girls and 111 boys. The study was conducted in two stages - medical examinations for all students and the assignment of peer medicine application supervisors. The research took place from February to August 2022 in Bandung city. The results demonstrated that the peer medicine application supervisor approach was highly effective in reducing the cases of scabies in the pesantren. Scabies cases decreased significantly from 58% to 27%. In conclusion, the implementation of the peer medicine application supervisor successfully reduced scabies cases in the Islamic boarding school setting. Keywords: Scabies elimination, peer medicine application supervisor, Islamic boarding school